2019
DOI: 10.22436/jmcs.019.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Permanence of a nonlinear mutualism model with time varying delay

Abstract: Sufficient conditions are obtained for the permanence of the following nonlinear mutualism model with time varying delay dN 1 (t) dt = r 1 (t)N 1 (t) K 1 (t) + α 1 (t)N β 1 2 (t − τ 2 (t)) 1 + N β 1 2 (t − τ 2 (t)) − N δ 1 1 (t − σ 1 (t)) , dN 2 (t) dt = r 2 (t)N 2 (t) K 2 (t) + α 2 (t)N β 2 1 (t − τ 1 (t)) 1 + N β 2 1 (t − τ 1 (t) − N δ 2 2 (t − σ 2 (t)) ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…where 1 1+ f y and m x+a stand for the fear effect and additive Allee effect, respectively; r is the intrinsic growth rate of prey; b is the predation rate; α is the conversion coefficient; and n is the death rate of the predator. As we known, the relationship between prey and predator has always been the focus of scholars [31][32][33][34][35][36][37]; hence, this paper will enrich the literature in this field.…”
Section: Introductionmentioning
confidence: 99%
“…where 1 1+ f y and m x+a stand for the fear effect and additive Allee effect, respectively; r is the intrinsic growth rate of prey; b is the predation rate; α is the conversion coefficient; and n is the death rate of the predator. As we known, the relationship between prey and predator has always been the focus of scholars [31][32][33][34][35][36][37]; hence, this paper will enrich the literature in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Haileyesus Tessema Alemneh formulated the epidemic model to investigate the dynamical behavior of maize streak virus and developed the control strategies [17]. A number of papers have discussed at least two species for delayed or non-delayed predator-prey models [18][19][20][21][22][23][24]. It has been shown that the majority of epidemiological models can be represented as a system of differential equations, with time lags frequently included [25,26].…”
Section: Introductionmentioning
confidence: 99%